Surfactant and respiratory distress syndrome - Milner, Anthony David (The Turkish Journal of Pediatrics, 1996)
Since the late 1950s it has been known that the cause of respiratory distress syndrome (RDS) is surfactant deficiency, especially in preterm infants. But surfactant protein B deficiency may cause RDS in term infants as well. Administration of natural surfactant produce is well known to a rapid improvement in oxygenation within 15 to 20 minutes. The effect of synthetic surfactant is less dramatic. Although randomized controlled trials have been done, the majority have been relatively small. Studies on the role of natural surfactant given to infants with established RDS (rescue therapy) have shown a reduction in the incidence of neonatal death and pneumothorax of 40% and 65%, respectively, compared to untreated infants. However, natural surfactant provides no apparent benefits in terms of the incidence of intraventricular hemorrhage (IVH), patent ductus arteriosus (PDA) or bronchopulmonary dysplasia (BPD). The results of synthetic surfactant given as rescue therapy have shown a similar effect with a 40% reduction in mortality and a 48% reduction in pneumothorax. However, synthetic surfactant also led to a 23% reduction in IVH, 27% in PDA, and 32% in BPD. When natural surfactant is given as prophylaxis (i.e. at or soon after birth, before the development of RDS), the reduction in mortality is 45% and the reduction in pneumothorax is 69%, but as with rescue therapy, there is no effect on the incidence of IVH or BPD. The effect on the incidence of PDA is an increase of 27%. When synthetic surfactants are given prophylactically, there is a similar reduction in mortality of 44% and a reduction in pneumothorax of 36%. The incidence of IVH and BPD is unchanged, but as with the natural surfactant, there is a small increase in the incidence of PDA of 27%. The main side effect is pulmonary hemorrhage that has been reported to occur in 4-7% of infants given surfactant. Although the administration of surfactant has had a dramatic effect on neonatal practice, it is likely that further studies will lead to more appropriate use of surfactant.
Keywords: surfactant; respiratory distress syndrome; mortality; morbidity; side effects